2018
DOI: 10.3390/jcm7080193
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Circulating 25OHD Fractions for Early Recovery and Survival in Patients with Hip Fracture

Abstract: The relation between vitamin-D (VD) status and healing after hip fracture had not been sufficiently addressed. Currently serum total 25-hydroxy-VD (t-25OHD) is the most widely used indicator of VD status. It is unclear whether free or bioavailable VD are better markers of 25OHD availability for tissues. Validity of overall cut-off values of t-25OHD is limited. Objectives: (1) Assess serum levels of circulating forms of 25OHD in patients with hip fracture (PwHF: N = 199) compared to active controls without hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
4
3
1
Order By: Relevance
“…Other authors have also found associations between 25(OH)D 3 levels and mortality. Toldy et al 19 , in a case-control study, had results similar to ours. Fisher et al 21 , in multivariate analyses, found seven variables that independently increased in-hospital mortality among patients treated for hip fracture, including serum 25(OH)D 3 levels below 25nmol/L.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other authors have also found associations between 25(OH)D 3 levels and mortality. Toldy et al 19 , in a case-control study, had results similar to ours. Fisher et al 21 , in multivariate analyses, found seven variables that independently increased in-hospital mortality among patients treated for hip fracture, including serum 25(OH)D 3 levels below 25nmol/L.…”
Section: Discussionsupporting
confidence: 88%
“…Considering that our state is geographically located close to the 30 th South parallel and the ethnic makeup of the southern Brazilian population is overwhelmingly white (>80%) 22 , studies assessing the effects of serum 25(OH)D 3 levels in patients with hip fractures are necessary. Our sample is similar to those previously reported in the literature in terms of age and sex 18 , 19 .…”
Section: Discussionsupporting
confidence: 85%
“… 17 , 18 Survival analysis indicated that the t-25OHD showed a tendency to predict survival, as the one-year mortality rate increased from 8% to 14% when comparing the t-25OHD deficiency group (≤16 ng/mL) and the control group. 14 In addition, a retrospective, total cohort study including 30,552 patients found that Vitamin D supplementation showed a moderate but significant influence on postoperative mortality in hip fracture patients, 29 which is in favor of our findings. However, the opposite side claimed that the four groups classified by quartiles of serum 25(OH)D did not differ in the one-year mortality of geriatric hip fracture patients.…”
Section: Discussioncontrasting
confidence: 46%
“…Currently, there is no consensus on the optimal cut-off values of t-25OHD for predicting clinical outcomes and the definition of adequate vitamin D status due to the different racial background. 14 , 34 Based on the results of an observational, cross-sectional analysis, which was conducted in healthy South Asian populations who were aged from 40 to 69 years, 92% of the patients (5918 in 6433) were classified as Vitamin D deficiency (<20 ng/mL) according to the criteria, which were primarily set based on Caucasian populations. 35 Consistently, we also found that the best cut-off values (16.21 ng/mL before PSM and 17.80 ng/mL after PSM) for predicting one-year mortality in south Chinese geriatric hip fracture patients were slightly lower than the commonly used cut-off thresholds of Vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation